Prevalence of nptII genes in three different soil fields in Tromsø - Steffensen, Andreas Ellingsen (UiT Norges arktiske universitet, 2015)
The main goal has been to establish methods to be able to study the rate of nptII in soil in Tromsø, in aerobe cultivation of bacteria and in soil DNA. Soil is a complex and diverse environment for bacteria, and it has all the qualities required to be a potential reservoir for antibiotic resistance genes. In collaboration with Bioforsk Tromsø we have gathered soil samples from soil where it has been used manure yearly, soil where it has been approx. seven years since it was used manure and soil where it has never been used manure as fertilizer. Out of totally 106-107 cultivable bacteria from the different soils, our results show that approx. 3-12% of the bacteria are Km resistant but none of the approx. 550 Km resistant bacteria we have analysed carry the nptII gene. Since only 1-2% of soil bacteria can be grown we also did a direct analysis of soil DNA from the three separate fields by isolating and purifying DNA from soil before running qualitative and quantitative PCR. The conclusion of our pilot study is that there is no or low rate of the nptII gene in bacteria and soil DNA in the three separate soils we have examined in Tromsø.